HUBUNGAN MASA KEJA, PENGETAHUAN PEKERJA DAN KETERSEDIAAN SARANA DENGAN KESIAPSIAGAAN TANGGAP DARURAT KEBAKARAN DI SHOP 1 PT. X KOTA BATAM - Jamal, Jamal; Fauzi, Asnil; Jading, Rasmin Nur; Permata, Hening Rizky; Parisma, Wan Intan (LPPM Universitas Ibnu Sina, 2025)
Period of work can influence a person's actions, in other words, tenure can influence knowledge. In this study, employees who have worked for a long time understand fire emergency response preparedness more quickly than new employees, which can be dangerous for workers if they know about fire emergency response actions. Good. The aim of this research is to find the relationship between work experience, knowledge and the availability of advice in the PT shop 1 area. X Batam City 2024. This research uses quantitative methods with a total population of 38 respondents. The sampling technique uses total sampling where the number of samples is the same as the total sampling. Statistical analysis uses the chi-square test with research instruments using questionnaires and observation sheets. The research results show a relationship between length of service and emergency response preparedness with a P value = 0.046, there is a relationship between knowledge and emergency response preparedness with a P value = 0.024, there is a relationship between the availability of facilities and emergency response preparedness with a P value = 0.002. expected from PT. X to conduct weekly or monthly inspections in order to ensure that each APAR functions well, providing an emergency response training at least every 6 months so that new employees understand the procedure of fire emergency response.